Mathematical model For the prediction of microwave signal attenuation due to duststorm - Elshaikh, Zain Elabdin Omer; Islam, Md. Rafiqul; Khalifa, Othman Omran; Abd-El-Raouf, Hany Essam (EMW Publishing, 2009)
The microwave signal attenuation caused by dust is one of the major problems in utilizing microwave bands for terrestrial and space communication especially at desert and semi desert area. This paper presents a mathematical model developed to characterize the microwave signal attenuation due to dust. This model enables a convenient calculation of the microwave signal path attenuation which relates attenuation to visibility, frequency, particle size and complex permittivity. The predicted values from the mathematical model, which are compared with the measured values observed by the author in Sudan show relatively optimistic agreement.